PEMBUATAN MEDIA PEMBELAJARAN MATEMATIKA UNTUK ANAK USIA 6-8 TAHUN BERBASIS ANDROID MENGGUNAKAN UNITY 3D - Waliya Rahmawanti (Jurnal Ilmiah Teknik, 2023)
This pandemic requires technology to enter into all aspects of life, including the education aspect. Advances in information technology certainly support various needs for delivering information in the field of education, one of which is the existence of game-based learning media. School learning which is often boring, in this pandemic situation, it is imperative to change it in a more fun way, especially in mathematics. The existence of learning media with anadroid-based games is expected to make it easier to understand learning to count addition. The game "Menjumlah Yuk" is made using Unity. This application provides a home page, instructions page, question page, info page, and destination page. This application has been tested based on the functionality of all the menus created.